2012
DOI: 10.1111/j.1365-2966.2012.21355.x
|View full text |Cite
|
Sign up to set email alerts
|

A pulsation zoo in the hot subdwarf B star KIC 10139564 observed by Kepler

Abstract: We present our analyses of 15 months of Kepler data on KIC 10139564. We detected 57 periodicities with a variety of properties not previously observed all together in one pulsating subdwarf B (sdB) star. Ten of the periodicities were found in the low-frequency region, and we associate them with nonradial g modes. The other periodicities were found in the highfrequency region, which are likely p modes. We discovered that most of the periodicities are components of multiplets with a common spacing. Assuming that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 28 publications
1
49
0
Order By: Relevance
“…Baran et al 2011) and that p-mode pulsator KIC 10139564 also shows g-mode pulsations while it has an effective temperature that is close to 32 000 K (Baran et al 2012, indicated with a black point on Fig. 5).…”
Section: Pressure and Gravity Mode Instability Stripsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baran et al 2011) and that p-mode pulsator KIC 10139564 also shows g-mode pulsations while it has an effective temperature that is close to 32 000 K (Baran et al 2012, indicated with a black point on Fig. 5).…”
Section: Pressure and Gravity Mode Instability Stripsmentioning
confidence: 99%
“…The black point indicates KIC 10139564 (Baran et al 2012), which is a hybrid pulsator that predominantly shows p-mode pulsations. The vertical dashed lines indicate the blue edges of the instability strips predicted by Jeffery & Saio (2006) and Hu et al (2009). hybrid pulsators that show both p-and g-mode pulsations in red.…”
Section: Pressure and Gravity Mode Instability Stripsmentioning
confidence: 99%
“…Indeed we do not see any signature of a magnetic field in our optical spectra or in the pulsation spectrum. Moreover, sdB stars have relatively long rotational periods, P ROT > 1 day from spectroscopy (Geier & Heber 2012), while values up to ∼40 days are obtained from pulsation rotational splitting (e.g., Baran et al 2012). This rules out all (known) alternatives other than orbitally driven modulations.…”
Section: Kepler Data and Ephemerismentioning
confidence: 99%
“…With a Kepler magnitude of 15.85, KIC 10001893 is one out of 19 subdwarf B (sdB) pulsators observed by the Kepler spacecraft in its primary mission , 2011, 2012Kawaler et al 2010a,b;Reed et al 2010Reed et al , 2011Reed et al , 2012Van Grootel et al 2010;Baran et al 2011Baran et al , 2012Charpinet et al 2011b). The spectroscopic atmospheric parameters of KIC 10001893, T eff = 26 700 ± 300 K, log g = 5.30 ± 0.04, and log (N He /N H ) = −2.09±0.1 are very compatible with the g-mode instability strip (Østensen et al 2011).…”
Section: Kepler Data and Ephemerismentioning
confidence: 99%
“…In addition, rotationally split multiplets have been used to identify the and m modes of pulsations [e.g. 6,7]. Stellar rotation lifts the frequency degeneracy and gives rise to frequency multiplets whose splittings follow the relation ∆ν = ∆mΩ(1 − C n, ).…”
Section: Introductionmentioning
confidence: 99%